Imagem da ultraestrutura e viabilidade de Candida albicans e espécies não-albicans vaginais aderidas ao dispositivo contraceptivo intrauterino através de microscopia eletrônica de varredura e microscopia confocal laser - Paiva, Luciene de Cassia Farias (2010)
Vulvovaginal candidiasis (VVC) is an infectious process of the female genitourinary tract, characterized by abnormal growth of yeasts that belong to the normal vaginal microbiota, and which could become pathogenic when unbalance of host defenses occur. The adherence and biofilm production are considered the main virulence factors associated to Candida species. Through adhesion, colonization of these yeasts occurs in several parts of the host organism, allowing the formation of biofilm. The adherence of yeasts to intrauterine device (IUD) could facilitate the development of VVC and recurrent VVC (RVVC) in susceptible patients who use this contraceptive method. The objective of this work was to evaluate the adhrence of C. albicans and species non-albicans isolated from vaginal exudate of patient with VVC in IUD, as well as the aspects of adhesion and viability of fungal cells throughout microscopical images obtained by scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). For the adherence assays, there were utilized vaginal isolates of C. albicans, C. glabrata, C. parapsilosis, C. guilliermondii, C. tropicalis and Saccharomyces cerevisiae. As specimens, there were used fragments of IUD (TCu 380A). SEM e CLSM demonstrated adhesion of all vaginal isolates in different parts of the IUD (tail, part without cupper, and part covered with cupper) and viability of yeasts in all specified conditions. It is concluded that all parts of IUD contribute to retention of yeasts in the genital tract. Besides that, high concentration of yeast cells in the string indicates the importance of this segment for the maintenance of yeasts in relation to vaginal site and also the possibility of their ascension to the uterus.